Catalytic Photodegradation of Cyclic Sulfur Compounds in a Model Fuel Using a Bench-scale Falling-film Reactor Irradiated by a Visible Light - Noor Edin Mousa; Seba S. Mohammed; Zainab Y. Shnain; Mohammad F. Abid; Asawer A. Alwasiti; Khalid A. Sukkar (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
A homemade N doped-TiO2 nanoparticle were used to degrade dibenzothiophene (DBT) in a model fuel flowing on a bench-scale glass-made falling film reactor irradiated by a xenon lamp that emitted visible light. The photocatalyst was immobilized on the glass sheet. EDS, SEM, and FT-IR techniques were utilized to identify the morphology of the N doped-TiO2 nanoparticles. Different operating parameters (e.g., N loading (0, 4, 5, and 6 wt%), light intensity (20, 40, and 60 W/m2), and pH (4, 7, and 10)) were investigated for their effect on the DBT degradation.  The effect of the N loading on the wettability of the nano-TiO2 particles was also investigated. Experimental results revealed that the N loading did not affect the wettability characteristics of the nano TiO2 particles. Moreover, results showed that DBT conversion positively depends on N loading, light intensity (hv), and pH increase. The estimated optimal operating parameters were 5 wt% N loading, pH = 10, and hv = 40 W/m2 to ensure the best photo-oxidation efficiency of 91.4% after 120 min of operation. The outcomes of the present work confirmed the effective efficiency of the N-doped TiO2 nanoparticles irradiated by visible light for DBT degradation. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).